FINANCIAL LITERACY, RISK PERCEPTION, MATERIALISM AND PROPENSITY TO INDEBTEDNESS - Pamungkas, Ary Satria; Herwindiati, Dyah Erny; Taba, Muhammad Idrus (International Journal of Application on Economics and Business, 2024)
The purpose of this paper is to study the influence of financial literacy, risk perception and materialism on propensity to indebtedness. The number of samples in this study was 200 respondents who were credit card users who already had income in the Jakarta area. For data analysis, this study used Structural Equation Modelling (SEM). The result of this study indicated that Financial Literacy and Risk Perception has a negative effect on Propensity to Indebtedness, while Materialism has a positive effect on Propensity to Indebtedness.